IMPROVING STUDENTS' ABILITY TO WRITE ANNOUNCEMENT TEXT USING THE PjBL MODEL IN GRADE X TITL STUDENTS AT SMKN 1 LOPOK - Nurfitriah, Nurfitriah (Journal of Educational Studies, 2023)
This study aims to improve students' ability to write announcement texts using the Project-based Learning (PjBL) learning model for grade X TITL students at SMKN 1 Lopok. This research was motivated by the low ability of students to write announcement texts that can affect school communication effectively. Therefore, the PjBL approach was chosen as a learning model that can provide an active, creative, and collaborative learning experience, so it is expected to improve students' ability to write announcement texts. The research method used is Classroom Action Research (PTK) with two cycles. The study participants consisted of 30 grade X TITL students at SMKN 1 Lopok. Data were collected through an announcement text writing test before and after the application of the PjBL model, as well as participatory observation and interviews to obtain qualitative data on student responses to learning. The results showed a significant improvement in students' ability to write announcement texts after applying the PjBL model. The average students' writing test scores increased from the first cycle to the second cycle. In addition, student responses to learning using the PjBL model were generally positive, with students expressing a sense of enthusiasm and satisfaction in learning that was more practical and relevant to everyday life. The application of the Project-based Learning (PjBL) learning model is effective in improving students' ability to write announcement texts in class X TITL at SMKN 1 Lopok.